Use of chatbots based on artificial intelligence for higher education - Ramirez Pastor, Jose Alex; Martinez Zambrano, Hilary Rosmery; Alarcón, Felipe; Rodriguez Alvarez, Silvia Rita (LACCEI, 2024)
Education has been evolving to the present day, allowing the use of technology and the diversity of digital tools to be incorporated into the training process of the higher education student. This is why the use of AI-based Chatbots in higher education is a constantly growing trend that is transforming the learning experience, as they help solve some of the current challenges faced in this sector. Therefore, we set out to evaluate the factors that affect the adoption of the use of AI-based Chatbots to improve the quality of student learning in higher education. For this reason, in this research, the quantitative method was used by collecting of data, for which inclusion and exclusion criteria were applied, 19 articles were selected from the IEEE and Scopus databases. The results showed that AI-based Chatbots offer personalization, instant interaction and fast, automated support to higher education students, as they can provide answers to frequently asked questions, guide students through available resources, assist in resolution of problems and offer reminders of tasks and deadlines. It was concluded that the research result will help Chatbot developers, higher education institutions and higher education providers to better understand the needs of students and at the same time provide them with an interactive learning and learning platform. communication.